The agriculture-nutrition-income nexus in Fiji - Lako, J.; Francis, Judith Ann; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2019)
Agriculture in Fiji contributes 9% of gross domestic product and absorbs 40% of the labour force. Over 70% of the population is engaged in subsistence and semi subsistence agriculture. Insufficient production capacity, inconsistent quality and limited knowledge of the nutrient and health benefits make local fruits, root crops, seafood and vegetables uncompetitive. Numerous policies, programmes and organisations shape the agriculture-nutrition-income agenda but with mixed results and very limited impact.